Flipped learning enhance technical and professional skills facilitating employability: a review of the evidence. (12th April 2019) - Ismail, Mohammed
The purpose of this paper is to provide a comprehensive review of the current state of knowledge and practice, and the impact flipped learning - intertwined with education technology has on engineering education. Result of the study indicates that flipped learning blended with education technology, brings about a highly collaborative and activity-based environment with indirect evidence of: improved academic performance, team-based learning, communication skills and group participation skill, critical thinking, that are important traits for employability. The study also provides empirical evidence about the use of education technology in flipped learning, but is not to the desired levels to offer the intended benefits. Flipped learning offers several challenges to the instructor and the students, but the benefits outweigh the challenges. The future scope for researchers would be to focus on the integration of the in-class and out-of-class activities.